The Effect of Workload and Work Environment on Employee Performance at PT Citra Surya Jaya - Faizin, Rahman; Saheri, Mohamad; Mayasari, Ema; Sari, Reny Mareta (Universitas STRADA Indonesia, 2025)
The decline in employee performance in the construction industry is predicted to continue to be a significant concern if internal company factors are not addressed immediately. High workloads and an unsupportive work environment are key issues that have the potential to reduce workforce productivity. This study aims to determine the effect of workload and work environment on employee performance at PT Citra Surya Jaya. This study used a quantitative approach with a cross-sectional design and involved 30 respondents using a total sampling technique. Data were collected using a standardized questionnaire and analyzed using multiple linear regression. The results showed that workload (p-value = 0.048 (<0.05)) and work environment (p-value = 0.000 (<0.05)) significantly influenced employee performance. Therefore, it is concluded that both variables are important factors in determining employee performance. Therefore, adjusting workload and improving the work environment require management attention in an effort to continuously improve employee performance.